EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN HIPERTENSI DI UPTD PUSKESMAS JUANDA KOTA SAMARINDA - Wijikinasih, Wijikinasih; Muh. Taufiqurrahman; Raymon Simanullang (Jurnal Riset Kefarmasian Indonesia, 2025)
The increasing use of antihypertensive drugs may raise the potential for irrational use. Irrational management of hypertension can worsen the patient’s condition and trigger complications such as stroke, heart disease, and kidney failure. This study was a descriptive study with retrospective data collection using purposive sampling. Data were obtained from electronic medical records in the e-Puskesmas application of hypertensive patients. The results showed that 85.8% of antihypertensive drug use was in accordance with hypertension management based on the Decree of the Minister of Health of the Republic of Indonesia No. HK.01.07/MENKES/1936/2022 on Clinical Practice Guidelines for Physicians in Primary Healthcare Facilities (PHC) and the JNC VIII Guidelines. These findings indicate that most antihypertensive drug use in primary healthcare facilities has followed current management standards, although approximately 14.2% of cases still demonstrate potential irrational use. This highlights the need for continuous evaluation and improved adherence to clinical guidelines in order to minimize the risk of complications.